Kompetensi pedagogik guru sekolah dasar sebagai pendukung program merdeka belajar - Eko Kuntarto; Maryono Maryono; Muhammad Sholeh (Universitas Kanjuruhan Malang, 2023)
This study aims to access the composition of the pedagogic competence of elementary school teachers as a supporter of teaching practice guidance (PLP) for PGSD students in carrying out school-based MBKM (Merdeka Belajar Kampus Merdeka) activities. The research instrument is a Teacher Competency Assessment Questionnaire which is designed with an online platform. The contents of the questionnaire are prepared based on the dimensions and indicators of pedagogical competence criteria which refer to the National Assessment of Indonesian Teacher Competence. Questionnaires were given to 40 PLP mentoring teachers who were selected based on a purposive random sampling technique, based on several criteria. The research method uses quantitative and qualitative. Based on the results of the study, it shows that: the pedagogic competence of elementary school teachers as supporters of the school-based MBKM program is in the middle order position.